Peran Orang Tua dalam Mendidik Anak Sejak Dini di Lingkungan Keluarga - Elza Zakiah Fitrah; Desvi Wahyuni (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Children are a gift and also a trust that Allah entrusts to His servants who will later be responsible in the afterlife. As a parent, it is your responsibility to educate your child from an early age. The purpose of this article is to explain the role of parents in raising children. The research in this paper uses library research methods. The conclusion from this research is that the family is the first place where children receive education. A child's character and personality are initially formed in the family. This includes moral education or teacher education, scientific education, religious education, children's rights, care and concern for children. Parents are role models for their children. Education is a commitment to building character and competence inside and outside school and making it something lasting in life. Providing education first is not only the responsibility of the school, but also parents and family, because it is the closest and most important place for children. The partnership between schools and parents cannot be separated. However, in reality, many parents do not understand their responsibilities towards their children. They feel that if they send their children to school, they have no responsibility for their education. The most obvious impact of parental negligence is that children are not interested in learning. To overcome this problem, the author tries to explore the relationship between parental responsibility and children's interest in learning.